Processing Performance and Economic Feasibility Profile of Jambal Roti Salted Fish in Pangandaran, West Java - Ananda Dwi Septian; Iwang Gumilar; Nora Akbarsyah; Ine Maulina (Universitas Islam Lamongan, 2026)
Pangandaran's abundant fishery resources require proper processing to prevent rapid spoilage, making preservation through jambal roti salted fish production crucial for both food security and local livelihoods. Jambal roti salted fish production has become a crucial economic activity for coastal communities in Pangandaran. This study aims to analyze the processing performance and economic feasibility of jambal roti salted fish production in Pangandaran, West Java. The study employed Good Manufacturing Practices (GMP), Sanitation Standard Operating Procedures (SSOP), and Hazard Analysis and Critical Control Point (HACCP) for processing performance analysis, while Cost-Benefit Analysis (CBA) was used for economic feasibility assessment. The results showed that the enterprise is economically viable, with a monthly profit of IDR 4.940.278 and a profitability rate of 15.44%. Additional economic indicators include a BCR of 1.18, payback period of 0.23 years, BEP (Q) of 54.19 kg/month, BEP (IDR) of IDR 4.142.927/month, and a production cost per unit of IDR 67.649/kg. However, the technical performance evaluation indicated only 47% compliance with GMP, SSOP, and HACCP standards, suggesting substantial room for improvement in food safety practices. In conclusion, while jambal roti production in Pangandaran is economically feasible, improvements in processing performance are necessary to ensure better food safety compliance and sustainability.